Postmortem blood and tissue concentrations of R- and S-enantiomers of methadone and its metabolite EDDP - Jantos, Ricarda; Skopp, Gisela (Forensic science international, 2013)
Body fluids and tissues in 16 methadone (MTD)-associated fatalities were investigated to find out whether analysis of MTD and its metabolite 2-ethylidine-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP) following enantioselective separation of both compounds may assist in the interpretation of MTD findings. Individual case histories were shortly described. R- and S-MTD as well as R- and S-EDDP concentrations were determined by chiral LC-MS/MS. In all cases under investigation total MTD was present in sufficient quantities to kill or to contribute to death; concentrations were highest in lungs (MTD) and kidneys (EDDP). It appears that both MTD and EDDP undergo postmortem redistribution. In three cases, only the pharmacologically active R-MTD isomer was present. R-MTD mainly contributing to the drug's pharmacological effects, the enantiomeric ratio of MTD and EDDP may indicate whether MTD intoxication might have contributed to death or not. Further, it may be helpful to establish whether racemic MTD or enantiomerically pure R-MTD has been administered last, especially if R/S-ratios of MTD and EDDP significantly differ. It could be shown, that in vivo racemization occurs for neither MTD nor EDDP in any body fluid or tissue sample. Significantly higher MTD R/S-ratios in femoral and heart blood were present in individuals having participated in a MTD maintenance program. Overall, R/S-ratios of MTD and EDDP allow a more detailed interpretation of analytical results in MTD-associated deaths. Thus, determination of MTD and EDDP by enantioselective methods and calculation of their R/S-ratios should be favored.
Gesehen am 24.03.2021